2021
DOI: 10.3390/cancers13194918
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Patients with Endometrial Cancer and Adenomyosis

Abstract: A better endometrial cancer (EC) prognosis in patients with coexistent adenomyosis has been reported. Unfortunately, it is still unclear if this better prognosis is related to a more favorable clinical profile of adenomyosis patients. We aimed to evaluate differences in the clinical profiles of EC patients with and without adenomyosis. A systematic review and meta-analysis was performed by searching seven electronics databases for all studies that allowed extraction of data about clinical characteristics in EC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…On the contrary, the neoplastic potential in adenomyosis is poorly understood, and has been mainly described in association with EC. The coincidence between these two diseases can be an effect of potential common risk factors, which may lead to hyper-estrogenic status (history of diabetes, hypertension, high BMI, and tamoxifen intake, but not nulliparity [ 58 ]) or by shared pathogenetic mechanisms, including genetic mutation and inflammatory factors that induce angiogenesis and cell proliferation, which promote carcinogenesis. According to the presented data, adenomyosis seems to be a favorable prognostic oncological factor when it occurs with EC, but the finding appears to be contradictory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, the neoplastic potential in adenomyosis is poorly understood, and has been mainly described in association with EC. The coincidence between these two diseases can be an effect of potential common risk factors, which may lead to hyper-estrogenic status (history of diabetes, hypertension, high BMI, and tamoxifen intake, but not nulliparity [ 58 ]) or by shared pathogenetic mechanisms, including genetic mutation and inflammatory factors that induce angiogenesis and cell proliferation, which promote carcinogenesis. According to the presented data, adenomyosis seems to be a favorable prognostic oncological factor when it occurs with EC, but the finding appears to be contradictory.…”
Section: Discussionmentioning
confidence: 99%
“…They found a better overall survival rate in EC-A, decreased ratio of Ib according to FIGO (deep myometrial invasion) (OR = 0.45; 95% CI = 0.33–0.60; p < 0.00001) or lymphovascular space invasion [ 57 ]. Worth mentioning is the fact that only parity and not other risk factors for EC differs between patients with EC coexisting with adenomyosis and EC alone [ 58 ].…”
Section: Clinical Studiesmentioning
confidence: 99%
“…In particular, differences in the prevalence of pathological, clinical and/or molecular prognostic factors between women with and without coexistent adenomyosis have been supposed. In detail, while clinical factors (with the exception for nulliparity) have shown no significant differences between endometrial cancer patients with and without adenomyosis, conventional pathological prognostic factors have been shown to be less frequently unfavorable in endometrial cancer patients with adenomyosis compared to endometrial cancer patients without adenomyosis [8,14]. However, to our knowledge, data about molecular prognostic factors (i.e., molecular groups) in endometrial cancer patients with coexistent adenomyosis have never been reported; thus, the impact of the molecular signature on the reported favorable prognosis of endometrial cancer patients with coexistent adenomyosis is unknown.…”
Section: Introductionmentioning
confidence: 92%
“…Endometrial cancer is the most frequent gynecological neoplasm in Western countries [1][2][3][4][5][6][7][8]. The risk stratification of endometrial cancer patients had been mainly based on post-surgical pathological prognostic factors prior to the introduction of the Cancer Genome Atlas (TCGA) Research Network molecular classification [9] and the Proactive Molecular Risk Classifier for Endometrial Cancer (ProMisE) [1,2,4,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…However, in other studies, adenomyosis with EC has been linked to early-stage malignancy and extended surveillance 7 . Furthermore, subsequent investigations have demonstrated that adenomyosis does not negatively affect the prognosis and questionnaires of EC patients 8,9 . It is therefore still unclear whether EC and adenomyosis are related.…”
Section: Introductionmentioning
confidence: 99%